(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article analyzes the development trends of the mortgage lending system in Uzbekistan in recent years. Changes in the volume of mortgage loans, interest rates, borrower composition, and market segments are examined. Additionally, government programs, innovations in banks’ mortgage policies, and their impact on the population’s living standards are discussed.